Respuesta :
Answer:
f(x) = -38
Step-by-step explanation:
well f(x) is the same thing as y so just write it as y so its easier to understand.
y = -2x -13
take the x value they give you which in this case is 5 and plug it in to the x in your equation.
y = -2(5) -13
now just use a calculator or something and find that
y = -25 - 13
and finally
y = -38
now just change y back to f(x) if needed
hope this helps :)
What helps with a problem like this is replacing f(x) with y. The equation becomes y=-2x-13. Now you just need to plug on for x. y=-2 (5)-13. that becomes y = -10 - 13. y= -23. you have to change y back to f(x) so, f(x) = - 23.